A class of new type unified non-differentiable higher order symmetric duality theorems over arbitrary cones under generalized assumptions - Dubey, Ramu; Kumar, Rajnish; Alam, Khursheed; Narayan, Mishra Lakshmi; Narayan, Mishra Vishnu (Yugoslav Journal of Operations Research, 2022)
In the present paper, a newly combined higher-order non-differentiable symmetric duality in scalar-objective programming over arbitrary cones is formulated. In literature we have discussed primal-dual results with arbitrary cones, while in this article, we have derived combined result with one model over arbitrary cones. The theorems of duality are derived for these problems under η-pseudoinvexity/η-invexity/C-pseudoconvexity/C-convexity speculations over arbitrary cones.